DAMPAK TERPAAN TAGAR #NOVIRALNOJUSTICE TERHADAP REPUTASI POLRI DENGAN PERSEPSI GENERASI Z PENGGUNA MEDIA SOSIAL X SEBAGAI VARIABEL MEDIASI - Rumaisa Himmatu Sholihah; wiwid Noor Rakhmad (Interaksi Online, 2026)
Law No. 2 of 2002 reflects the government’s efforts to ensure public safety and order through the role of the Indonesian National Police in preventing and addressing all forms of legal violations. However, in practice, certain actions by the Indonesian National Police remain inconsistent with the principles enshrined in the 1945 Constitution. The #NoViralNoJustice hashtag phenomenon on social media represents the escalation of public criticism regarding the Indonesian National Police’s performance in law enforcement. The high intensity of this information exposure shapes Generation Z’s cognitive construction in interpreting and evaluating the institution. The study employed a quantitative approach with a positivist paradigm and utilized Partial Least Squares (PLS) analysis. The results indicate that exposure to the hashtag does not have a significant direct effect on reputation but does have a significant effect on perception. Furthermore, perception influences reputation and acts as a full mediator in the relationship between exposure and reputation. These findings confirm that institutional reputation is not formed instantly through media exposure, but rather through an evaluative process mediated by the construction of perceptions as a result of cognitive processing of the information received.